IMPACT OF FIRM CHARACTERISTICS ON ENVIRONMENTAL PERFORMANCE OF LISTED CONSUMER GOODS FIRMS IN NIGERIA - Tanko, Aliyu Ahmed; Muhammad, Muhammad Liman; Maigoshi, Zaharaddeen Salisu Maigoshi; Olanisebe, Moses Babatunde (Kashere Journal of Management Sciences, 2024)
This study examines the impact of firm characteristic on environmental performance of listed consumer goods firms in Nigeria. The study uses sixteen out of twenty listed consumer goods firms in Nigeria, and adopts correlational research design. Data for the study was extracted from the annual reports and accounts of the sampled firms for a period of 13 years from 2010 to 2022, and analyzed using multiple regressions. The results from the statistical analysis reveal a significant impact of firm characteristics (leverage, tangibility and firm size) on environmental performance using waste management cost while profitability, firm age and liquidity have insignificant impact on environmental performance of the sampled companies. The study concludes that leverage, tangibility and firm size affect environmental performance of the listed consumers’ goods companies in Nigeria. Based on this, this study recommends that management of listed consumer goods companies in Nigeria should take into account factors such as leverage, tangibility and firm size when deciding on to spend on waste management for environmental performance. Also, the management should embrace environmental performance practice in their plan which may elevate a company's image, engender trust, and secure its place as a frontrunner in the race towards a sustainable and profitable future. This implies that companies in line with their attributes should develop business models and strategies that will ensure environmental sustainability practice